1995
DOI: 10.1056/nejm199503163321104
|View full text |Cite
|
Sign up to set email alerts
|

Association between Cigarette Smoking and Mutation of the p53 Gene in Squamous-Cell Carcinoma of the Head and Neck

Abstract: In our study, a history of tobacco and alcohol use was associated with a high frequency of p53 mutations in patients with squamous-cell carcinoma of the head and neck. Preliminary evidence linked cigarette smoking to p53 mutations at nonendogenous mutation sites. Our findings suggest a role for tobacco in the molecular progression of squamous-cell carcinoma of the head and neck and support the epidemiologic evidence that abstinence from smoking is important to prevent head and neck cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

22
319
5
15

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 579 publications
(361 citation statements)
references
References 28 publications
22
319
5
15
Order By: Relevance
“…The biological mechanisms underpinning this association are not fully understood, but increased tumour hypoxia, resulting from increased carboxyhaemoglobin (the binding of carbon monoxide to haemoglobin) in smokers, is a likely explanation 43. In addition to this, it has been suggested that tobacco reduces the efficacy of radiotherapy through triggering a p53 mutation that could promote resistance to apoptosis 44. Smoking is also known to effect inflammatory responses45 and immune competence,46 which could increase the likelihood of adverse clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The biological mechanisms underpinning this association are not fully understood, but increased tumour hypoxia, resulting from increased carboxyhaemoglobin (the binding of carbon monoxide to haemoglobin) in smokers, is a likely explanation 43. In addition to this, it has been suggested that tobacco reduces the efficacy of radiotherapy through triggering a p53 mutation that could promote resistance to apoptosis 44. Smoking is also known to effect inflammatory responses45 and immune competence,46 which could increase the likelihood of adverse clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showing a positive association between TP53 mutation and tobacco smoke in patients with head and neck carcinoma are, however, more numerous e.g. [32-36] than studies with no association e.g. [38,58,59].…”
Section: Discussionmentioning
confidence: 99%
“…9,[15][16][17] In head and neck squamous cell carcinoma (SCC), a number of reports have documented overexpression of p53 protein 18 -21 and p53 gene mutation. 16,19,[22][23][24][25] However, conflicting results have been presented with regard to the correlation between prognosis and overexpression of p53. Some studies showed no correlation, 19,26 -28 whereas others showed a significant correlation between p53 expression and prognosis.…”
mentioning
confidence: 99%